POIESIS AS A DECISION-MAKING: SHKLOVSKY, TYNIANOV, BAKHTIN - Steiner, Petr (Bohemica Olomucensia, 2021)
This essay deals with the theories of Viktor Shklovsky and Iurii Tynianov from the perspective of decision science. It outlines how these two members of the Petersburg "Society for the Study of Poetic Language" (OPOIAZ) conceived of the writer as a rational agent pursuing a specific goal, and of the means at his/her disposal to attain it. Their approaches, the paper illustrates, correspond closely with two specific types of rationality: "instrumental" and "bounded". To conclude, the essay juxtaposes the Formalists' conceptualization of poetic creativity with Mikhail Bakhtin's view on the subject arguing that the way he conceives of the strategies available to the literary author fit the label of "interactive rationality".
Keywords: Bakhtin; Shklovsky; Tynianov; decision science; rationality.